"Do-not-touch" lesions of bone revisited. Issue 3 (March 2022) - Hegde, G.; Azzopardi, C.; Patel, A.; Davies, A.M.; James, S.L.; Botchu, R.
Abstract : Incidental bone lesions are encountered frequently in day-to-day practice. Many of these lesions are indeterminate requiring referral to specialist centres for further characterisation with or without biopsy; however, as biopsy has its own drawbacks, not all lesions can be subjected to biopsy. The primary role of a radiologist in these situations is to characterise these lesions based on their imaging appearances into aggressive lesions requiring biopsy and non-aggressive lesions that do not require a biopsy. The term "do-not-touch lesion" is used to describe a lesion with typical radiographic appearances that can be characterised based on radiographic appearances alone without needing a biopsy. With recent advances in imaging, many incidental lesions can be characterised into do-not-touch lesions based on their imaging appearances alone using a single imaging technique or using a combination of imaging techniques and, less frequently, with the additional help of serological investigations, without the need for biopsy. Hence, the definition of do-not-touch lesions of bone needs a revisit. In this article, we attempt to redefine do-not-touch lesions of bone and propose an imaging-based classification for characterisation of these lesions.